Tumour MLH1 promoter region methylation testing is an effective prescreen for Lynch Syndrome (HNPCC). Issue 12 (3rd October 2014) - Newton, K; Jorgensen, N M; Wallace, A J; Buchanan, D D; Lalloo, F; McMahon, R F T; Hill, J; Evans, D G
Abstract : Background and aims: Lynch syndrome (LS) patients have DNA mismatch repair deficiency and up to 80% lifetime risk of colorectal cancer (CRC). Screening of mutation carriers reduces CRC incidence and mortality. Selection for constitutional mutation testing relies on family history (Amsterdam and Bethesda Guidelines) and tumour-derived biomarkers. Initial biomarker analysis uses mismatch repair protein immunohistochemistry and microsatellite instability. Abnormalities in either identify mismatch repair deficiency but do not differentiate sporadic epigenetic defects, due to MLH1 promoter region methylation (13% of CRCs) from LS (4% of CRCs). A diagnostic biomarker capable of making this distinction would be valuable. This study compared two biomarkers in tumours with mismatch repair deficiency; quantification of methylation of the MLH1 promoter region using a novel assay and BRAF c.1799T>A, p.(Val600Glu) mutation status in the identification of constitutional mutations. Methods: Tumour DNA was extracted (formalin fixed, paraffin embedded, FFPE tissue) and pyrosequencing used to test for MLH1 promoter methylation and presence of the BRAF c.1799T>A, p.(Val600Glu) mutation 71 CRCs from individuals with pathogenic MLH1 mutations and 73 CRCs with sporadic MLH1 loss. Specificity and sensitivity was compared. Findingss: Unmethylated MLH1 promoter: sensitivity 94.4% (95% CI 86.2% to 98.4%), specificity 87.7% (95% CI 77.9% to 94.2%), Wild-type BRAF (codon 600): sensitivity 65.8% (95% CI 53.7% to 76.5%), specificity 98.6% (95% CI 92.4% to 100.0%) for the identification of those with pathogenic MLH1 mutations. Conclusions: Quantitative MLH1 promoter region methylation using pyrosequencing is superior to BRAF codon 600 mutation status in identifying constitutional mutations in mismatch repair deficient tumours.